"Keep Talking, I Keep Changing My Mind": The Value of Invitational Rhetoric for Focus Group Research. Issue 3 (27th May 2021) - Johnson, Jenell; Friz, Amanda; Randall, Caelyn; Vitolo-Haddad, CV
Abstract : This essay examines the unique place of focus groups within the recent turn to field methods in rhetorical studies and argues for a rhetorical theory of the action that takes place there. Using the design and data from a focus group study the authors conducted on ethical discussions of gene editing, it theorizes the group dynamics and rhetorical action of focus groups using Foss and Griffin's theory of invitational rhetoric, and argues that an invitational approach may help scholars to better appreciate focus groups not only as a method of rhetorical studies but also as an original site of rhetorical action.